2021
DOI: 10.3390/jpm11060575
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Aberrant Glycosylation of Serum Haptoglobin for Gastric Cancer Diagnosis Using a Middle-Up-Down Glycoproteome Platform

Abstract: Gastric cancer is a frequently occurring cancer and is the leading cause of cancer-related deaths. Recent studies have shown that aberrant glycosylation of serum haptoglobin is closely related to gastric cancer and has enormous potential for use in diagnosis. However, there is no platform with high reliability and high reproducibility to comprehensively analyze haptoglobin glycosylation covering microheterogeneity to macroheterogeneity for clinical applications. In this study, we developed a middle-up-down gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…In conclusion, optimal conditions for Hp N-glycans release and et al, 2012). Not all of these less complex glycans reported by O'Flaherty et al were recently confirmed on a glycopeptide level (Chandler et al, 2013;Jeong et al, 2021;Pompach et al, 2013), so their presence in low abundance could be explained by contamination from other plasma proteins, as well as at least partially by the differences in used methodological approaches.…”
Section: Optimization Of Hp N-glycans Release and Labelingmentioning
confidence: 95%
See 1 more Smart Citation
“…In conclusion, optimal conditions for Hp N-glycans release and et al, 2012). Not all of these less complex glycans reported by O'Flaherty et al were recently confirmed on a glycopeptide level (Chandler et al, 2013;Jeong et al, 2021;Pompach et al, 2013), so their presence in low abundance could be explained by contamination from other plasma proteins, as well as at least partially by the differences in used methodological approaches.…”
Section: Optimization Of Hp N-glycans Release and Labelingmentioning
confidence: 95%
“…Before lectin microarray enrichment (Miura et al, 2018) and 2‐DE, another option was a depletion of plasma of most abundant proteins like albumin and immunoglobulin G (IgG) or even sequential capturing of plasma proteins and their glycosylation analysis (Klein et al, 2010; O'Flaherty et al, 2019; Wilson et al, 2002; Zhao et al, 2007). Moreover, methods for Hp purification and enrichment established so far were generally low‐throughput, limited to individual sample preparation using affinity columns, and applied to a few dozen samples (Jeong et al, 2021; Pompach et al, 2013), therefore we are still lacking a fast and efficient method for large‐scale studies tackling Hp N‐glycosylation changes in different diseases or population studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to abundant alterations in the proteome, posttranslational modifications (PTMs) of proteins deserve attention in early detection of diseases and their monitoring. Glycosylation is one of the most important PTMs and plays a critical role in various biological processes, such as protein function and cell-cell interaction, which makes it as an important biomarker for cancer and infectious diseases [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, they function as important modulators for cellcell interaction and influence the fate and behaviors of these cells [4]. To improve the specificity and sensitivity of diagnosis, some studies have been directed toward the in-depth characterization of glycosylation of specific target glycoproteins [3,5]. It is important to note that direct analysis of intact glycoproteins, rather than glycan profiling, which is still considered the gold standard for its high throughput and sensitivity, accounts advantageous because of its simplicity, ease of sample preparation, and analysis time saving.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation